Tunable Syngas Production from CO2 and H2O in an Aqueous Photoelectrochemical Cell. Issue 46 (14th October 2016) - Chu, Sheng; Fan, Shizhao; Wang, Yongjie; Rossouw, David; Wang, Yichen; Botton, Gianluigi A.; Mi, Zetian
Abstract: Syngas, the mixture of CO and H2, is a key feedstock to produce methanol and liquid fuels in industry, yet limited success has been made to develop clean syngas production using renewable solar energy. We demonstrated that syngas with a benchmark turnover number of 1330 and a desirable CO/H2 ratio of 1:2 could be attained from photoelectrochemical CO2 and H2 O reduction in an aqueous medium by exploiting the synergistic co‐catalytic effect between Cu and ZnO. The CO/H2 ratio in the syngas products was tuned in a large range between 2:1 and 1:4 with a total unity Faradaic efficiency. Moreover, a high Faradaic efficiency of 70 % for CO was acheived at underpotential of 180 mV, which is the lowest potential ever reported in an aqueous photoelectrochemical cell. It was found that the combination of Cu and ZnO offered complementary chemical properties that lead to special reaction channels not seen in Cu, or ZnO alone. Abstract : Mixture is better : Syngas (CO+H2 ) with tunable composition is synthesized from the reduction of CO2 and H2 O in an aqueous photoelectrochemcal cell. A turnover number of 1330 and a high Faradaic efficiency of 70 % for CO at underpotential of 180 mV are acheived. The excellent perfomance is attributed to the coupling effects of strong light harvesting of p‐n Si, efficient electron extraction of GaN nanowires, and fast surface reaction kinetics of Cu–ZnO co‐catalysts.